Clinical Update of Severe Fever with Thrombocytopenia Syndrome - Jun-Won Seo; Dayoung Kim; Nara Yun; Dong-Min Kim (Viruses, 2021)
Severe fever with thrombocytopenia syndrome (SFTS) is an acute febrile illness characterized by fever, leukopenia, thrombocytopenia, and gastrointestinal symptoms such as diarrhea, nausea, and vomiting resulting from infection with the SFTS virus (SFTSV). The SFTSV is transmitted to humans by tick bites, primarily from Haemaphysalis longicornis, Amblyomma testudinarium, Ixodes nipponensis, and Rhipicephalus microplus. Human-to-human transmission has also been reported. Since the first report of an SFTS patient in China, the number of patients has also been increasing. The mortality rate of patients with SFTS remains high because the disease can quickly lead to death through multiple organ failure. In particular, an average fatality rate of approximately 20% has been reported for SFTS patients, and no treatment strategy has been established. Therefore, effective antiviral agents and vaccines are required. Here, we aim to review the epidemiology, clinical manifestations, laboratory diagnosis, and various specific treatments (i.e., antiviral agents, steroids, intravenous immunoglobulin, and plasma exchange) that have been tested to help to cope with the disease.